Combination of Fe(OH)3 modified diatomaceous earth and qPCR for the enrichment and detection of African swine fever virus in water - Wu, Hao; Tian, Zihan; Yao, Lun; Ghonaim, Ahmed H.; Chen, Xiaoyu; Ruan, Shengnan; Li, Huimin; Li, Wentao; He, Qigai (Frontiers in Veterinary Science, 2022)
Water is one of the primary vectors for African swine fever virus (ASFV) transmission among swine herds. However, the low concentrations of ASFV in water represent a challenge for the detection of the virus by conventional PCR methods, and enrichment of the virus would increase the test sensitivity. In this study, a rapid and efficient water-borne virus enrichment system (MDEF, modified diatomaceous earth by ferric hydroxide colloid) was used to enrich ASFV in water. After enrichment by MDEF, conventional real-time PCR (qPCR) was used for ASFV detection. ASFV were inactivated and diluted in 10 L of water, of which 4 mL were collected after 60 minutes using the MDEF system. Two thousand times reduction of the sample volume was achieved after enrichment. A high adsorption rate of about 99.99 (± 0.01)% and a high recovery rate of 64.01 (± 10.20)% to 179.65 (± 25.53)% was achieved by using 1g modified diatomaceous earth for 10 L ASFV contaminated water. The limit of qPCR detection of ASFV decreased to 1×10-1.11 GU ml-1 (genomic units per milliliter) from 1×102.71 GU ml-1 after concentrating the spiked water from 10 L to 4 ml. Preliminary application of MDEF allowed successful detection of african swine fever virus (ASFV), porcine circovirus type 2 (PCV2), and pseudorabies virus (PRV) in sewage. Thus, the combination of modified diatomaceous earth and real-time PCR is a promising strategy for the detection of viruses in water.